Estimating PM2.5 in Fort Collins, Colorado using a robust drive-by correction of low-cost air quality monitors deployed on school buses - Priyanka deSouza; Jessa Ellenburg; Andrew Turnipseed; Craig Williford; Helena Pliszka; Story Schwantes; Timothy Dye; Luke Greenidge; Austin Bailly; Thomas Kopala; Evan Vaughan; Michael Samon; et al. (Science of The Total Environment, 2025)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Participation in genetic research among Latinx populations by Latin America birth-residency concordance: a global study - Timothy De Ver Dye; Zahira Quiñones Tavarez; José G Pérez Ramos; Isabel Diana Fernandez; Carmen Vélez Vega; Denisse M Vega Ocasio; Esteban Avendaño; Nancy R Cardona Cordero; Carmen DiMare Hering; Ann M. Dozier; Susan W. Groth (Journal of Community Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Evaluating the implementation of cervical cancer screening programs in low-resource settings globally: a systematized review - J. Andrew Dykens; Jennifer S. Smith; Margaret Demment; E. Marshall; Tina Schuh; Karen Peters; Tracy Irwin; Scott McIntosh; Angela Sy; Timothy Dye (Cancer Causes & Control, 2020)
Purpose Cervical cancer disproportionately burdens low-resource populations where access to quality screening services is limited. A greater understanding of sustainable approaches to implement cervical cancer screening services is needed. Methods We conducted a systematized literature review of evaluations from cervical cancer screening programs implemented in resource-limited settings globally that included a formal evaluation and intention of program sustainment over time. We categorized the included studies using the continuum of implementation research framework which categorizes studies progressively from “implementation light” to more implementation intensive. Results Fifty-one of 13,330 initially identified papers were reviewed with most study sites in low-resource settings of middle-income countries (94.1%) ,while 9.8% were in low-income countries. Across all studies, visual inspection of the cervix with acetic acid (58.8%) was the most prevalent screening method followed by cytology testing (39.2%). Demand-side (client and community) considerations were reported in 86.3% of the articles, while 68.6% focused scientific inquiry on the supply side (health service). Eighteen articles (35.3%) were categorized as “Informing Scale-up” along the continuum of implementation research. Conclusions The number of cervical cancer screening implementation reports is limited globally, especially in low-income countries. The 18 papers we classified as Informing Scale-up provide critical insights for developing programs relevant to implementation outcomes. We recommend that program managers report lessons learnt to build collective implementation knowledge for cervical cancer screening services, globally.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)